Biological Activity of Apian Extracts Depending on the Way of Obtaining - Ermakova, N. Yu.; Kadnikova, N. G.; Roshal, A. D.; Synchykova, O. P.; Shinder, A. V.; Sandomirsky, B. P. (Problems of Cryobiology and Cryomedicine, 2006)
The composition and biological activity of the extracts derived from dead bees have been studied. Qualitative and quantitative compositions of the extracts were found by spectral and chromatography methods. Antioxidative activity was assessed with chemiluminescent method using ethers of acridine carbon acid. Saccharamyces cerevisiae were the test systems to examine biological activity of the extracts. Flavonoids and carotenoids having antioxidant properties were found to be components of the extracts. All studied extracts are characterized with biological activity depending on the way of extract obtaining.